Answer:
x=-16
Step-by-step explanation:
x/4-3=-7
x/4=-4
x=-16
Answer:
= a⁸/b⁻¹⁰
Step-by-step explanation:
Simplify the expression
(a^2b^-3/a^-2b^2)^2
= a⁴b⁻⁶/a⁻⁴b⁴
Using the law of indices
= a⁴⁻⁽⁻⁴⁾/b⁻⁶⁻⁴
= a⁴⁺⁴/b⁻¹⁰
= a⁸/b⁻¹⁰
The slope is 3.
10 - 7 = 3
4 - 3 = 1
Final step is to do 3 divided by 1 and you get 3.
Answer:
n = 0
Step-by-step explanation:
Anything to the power of 0 is 1
x^12 is already equal to x^12 so it only needs to be multiplied by 1
So n = 0
Answer:0 = 3x - 21
Step-by-step explanation:
From this given function we can take an
x
common from its expression
i.e
x
2
−
6
x
=
x
(
x
−
6
)
As we know that the product of two numbers is zero,when either one of them is zero
then in the above expression that we just factorised
the function can be zero when either
x
=
0
or when
x
=
6
i.e when
x
=
0
,
0
(
0
−
6
)
=
0
when
x
=
6
,
6
(
6
−
6
)
=
6
(
0
)
Finally, our prize of all that math, the zeroes of the function are
0
and
6
these numbers are called the zeroes of the function because when you put these values in
x
the function gives zero.